Loss of SPARC dysregulates basal lamina assembly to disrupt larval fat body homeostasis in Drosophila melanogaster. - Shahab, J.; Baratta, C.; Scuric, B.; Godt, D.; Venken, K.J.; Ringuette, M.J. (Developmental Dynamics, 2015)
SPARC is a collagen-binding glycoprotein whose functions during early development are unknown. We previously reported that SPARC is expressed in Drosophila by hemocytes and the fat body (FB) and enriched in basal laminae (BL) surrounding tissues, including adipocytes. We sought to explore if SPARC is required for proper BL assembly in the FB. SPARC deficiency leads to larval lethality, associated with remodeling of the FB. In the absence of SPARC, FB polygonal adipocytes assume a spherical morphology. Loss-of-function clonal analyses revealed a cell-autonomous accumulation of BL components around mutant cells that include collagen IV (Col lV), Laminin, and Perlecan. Ultrastructural analyses indicate SPARC-deficient adipocytes are surrounded by an aberrant accumulation of a fibrous extracellular matrix. Our data indicate a critical requirement for SPARC for the proper BL assembly in Drosophila FB. Since Col IV within the BL is a prime determinant of cell shape, the rounded appearance of SPARC-deficient adipocytes is due to aberrant assembly of Col IV. Developmental Dynamics 244:540-552, 2015. © 2014 Wiley Periodicals, Inc.